Utilization and determinants of maternity waiting homes among pastoralist mothers in Dire district, southern Ethiopia: a mixed-methods study - Hassan Mahamad Duba; Mulugeta Mekuria; Erean Shigign Malka; Addisu Waleligne Tadesse; Ketema Gashaw; Ketema Eshetu (Frontiers in Global Women's Health, 2024)
BackgroundMaternity waiting homes are cost-effective, World Health Organization-approved components of comprehensive prenatal, delivery, and postpartum care strategies. However, few community-based studies within Ethiopia's pastoralist communities, and none in the study area, have been conducted to determine actual usage or to gain a thorough understanding of the factors influencing utilization.MethodsA cross-sectional study, supplemented by qualitative methods, was conducted from June 25 to July 25, 2023. A simple random sampling technique was used to select 305 study participants. Data were gathered through an interviewer-administered questionnaire, entered into Epi-data version 3.1, and analyzed using SPSS version 25. Descriptive data were presented in tables, graphs, text, and percentages. Bivariate logistic regression identified candidate predictors at a P-value of <0.25, and predictors of maternity waiting home utilization were identified through multivariate logistic regression at a 95% confidence interval and P-value of <0.05. Qualitative interviews were transcribed, translated, and thematically analyzed.ResultsThe prevalence of maternity waiting home use in the study area was 35.2% (95% CI: 30.9%, 39.5%). Factors associated with maternity waiting home utilization included travel time greater than 60 min to nearby health facilities (AOR: 5.47 CI: 1.77, 16.91), good knowledge of danger signs of pregnancy (AOR: 5.41, CI: 1.86, 15.79), lack of a caretaker to household tasks (AOR: 0.1, CI: 0.03, 0.31), and a refusal to accept a waiting time of 2–4 weeks (AOR: 0.24 CI: 0.08, 0.74). The qualitative findings underscored hurdles such as resource constraints, challenges in providing maternity services, and the importance of community awareness and access to network connectivity in ensuring safe childbirth.ConclusionThis study aims to determine the utilization of maternity waiting homes and the factors associated with their use among women who gave birth within the last year in the Dire district, Borana zone, southern Ethiopia. The prevalence of maternity waiting home use was low compared to national efforts to promote this service. Longer travel time, lack of a caretaker, good knowledge of danger signs of pregnancy, and a refusal to accept a waiting time of 2–4 weeks were associated with maternity waiting home use in this study.